Generation Z's Perception of Religious Tolerance and Implementing Islamic Law in Indonesia - Aprilianto, Dwi; Aslamiyah, Siti Suwaibatul; Zahidi, Salman; Crisnasari, Nihaya Alifiya; Hidayatussholihah, Rahil (Institut Agama Islam Negeri Curup, 2025)
This research discusses Generation Z's (Gen-Z's) views on religious tolerance and the application of Islamic law in Indonesia. Also, it explores their perceptions of interreligious social relations in Indonesia, especially in Eat Java Lamongan and Surabaya, opinions about non-Muslim leaders, the Islamic State of the Caliphate, and opinions about the implementation of Islamic law in Indonesia, such as hand cutting and the death penalty. The research method is interesting because it combines quantitative and qualitative methods with a phenomenological approach to understand the complexity of Gen-Z's understanding of this issue. The study began with a quantitative survey to obtain an overview of Gen-Z's tolerant attitudes in Lamongan and Surabaya. After a quantitative survey, in-depth interviews were conducted. The research results show that Gen-Z has a positive attitude towards diversity and tolerance. However, there are still some respondents who doubt or disagree, especially regarding the acceptance of non-Muslim leaders and the application of Islamic law. This research concludes the importance of inclusive education in building tolerance and supporting harmonious social relations in a multicultural society. The majority of Gen-Z are open-minded and make friends with non-Muslims because they are accustomed to interacting with friends of different religions. There is a balanced comparison between Gen-Z, who reject the implementation of Islamic law and all its instruments because they consider this a pluralistic country, and it is impossible to impose regulations or laws on one religion. Meanwhile, Gen-Z accepted it because they felt disappointed with many crimes, so they thought one solution was to apply Islamic law.